The Oxford handbook of Christianity and the law - Witte, John; Domingo, Rafael (Oxford handbooks online Religion, 2024)
"This volume tells the story of the interaction between Christianity and law-historically and today, in the traditional heartlands of Christianity and around the globe. Sixty new chapters by leading scholars provide authoritative but accessible accounts of foundational Christian teachings on law and legal thought over the past two millennia; the current interaction and contestation of law and Christianity on all continents; how Christianity shaped and was shaped by core public, private, penal, and procedural laws; various old and new forms of Christian canon law, natural law theory, and religious freedom norms; Christian teachings on fundamental principles of law, politics, and legal order; and Christian contributions to controversial legal issues. Together, the chapters make clear that Christianity and law have had a perennial and permanent influence on each other over time and across cultures, albeit with varying levels of intensity and effectiveness"--